A produção intelectual de marketing em responsabilidade socioambiental empresarial: um estudo nos anais dos congressos da ANPAD de 1998-2012 - Medina, Erica Aita Bergel (2013)
The purpose of this study is to analyze the national Marketing research focused in Corporate Social and Environmental Responsibility - CSR, published in EMA, 3Es, ENEO, and EnANPAD conferences, held by ANPAD National Association of Post-Graduation and Research in Business Administration. A bibliometric analysis covering fifteen years, from 1998 to 2012, has resulted in the selection of 112 articles, assessed according to authorship, bibliographic references and sources, as well as theme suitability to the theory presented in this study. In order to achieve a correct selection and analysis of all articles, a thorough theoretical study took place aiming the comprehension of how CSR and Marketing relate, involving all required Marketing subdisciplines. It uses as initial framework the Sustainable Marketing tripod, consisted of social marketing, green marketing and critical marketing. It found no barriers or problems regarding green marketing and critical marketing theories. However, while analyzing social marketing, it was necessary to mention several existing subclassifications, leading to a theoretical widening regarding social marketing, cause-related marketing, societal marketing, and corporate societal marketing. The complete study analyzes thoroughly all selected papers, differing the two themes which it relates to, as well as the difficulties of such themes to researchers, due to several classifying contradictions found in articles. The concepts of sustainable consumption and CSR are also part of the theoretical framework. The study concluded mainly that bibliometrics showed a myriad of references to few authors, attesting Lotka s law; the reference framework, being plausible as reference to future studies; the comparison between study s and authors theory, the later which presents gaps specially regarding social marketing and corporate societal marketing themes; and the progress of researches in the subject. The study s limitations and working suggestions are also presented.